University Physics I Classical Mechanics - Gea-Banacloche, Julio (Open textbook library., 2019)
This is a “minimalist” textbook for a first semester of university, calculus-based physics, covering classical mechanics (including one chapter on mechanical waves, but excluding fluids), plus a brief introduction to thermodynamics. The presentation owes much to Mazur’s The Principles and Practice of Physics: conservation laws, momentum and energy, are introduced before forces, and one-dimensional setups are thoroughly explored before two-dimensional systems are considered. It contains both problems and worked-out examples.